AN ANNOTATED TRANSLATION OF IDIOMATIC EXPRESSION IN NOVEL SEE ME BY NICHOLAS SPARKS - Ariza Purnawati (Jurnal Sosial Humaniora dan Pendidikan, 2023)
This research is an annotated translation of idiomatic expression. The object of the research is a novel entitled See Me by Nicholas Spark. This novel contains many idioms which have different form in target language (Indonesian) when it comes to the context of use. The purposes of this research is to find out the difficulties faced by the researcher as a translator while translating idiomatic expression in the texts of novel See Me by giving plausible solution of the difficulties. The researcher uses the introspective and retrospective methods in conducting this annotated translation research. This research uses translation of idiomatic expressions of Baker’s idiomatic translation strategies to find the proper translating of idiomatic expressions. The result of this research is that from 10 data, there are 3 data of similar meaning but dissimilar form, 6 data translation by paraphrase, and 1 datum of similar meaning and form.